Distribution of Leptodiaptomus novamexicanus (Copepoda: Calanoida) in a Mexican hyposaline lake - Lugo, Alfonso; González, Ma. Eugenia; Sánchez, Ma. del Rosario; Alcocer, Javier (Revista de Biología Tropical, 1999)
The temporal and vertical fluctuation of the planktic copepod Leptodiaptomus novamexicanus was surveyed in a Mexican saline crater-lake. A one year monthly sampling was made between August 1993 and July 1994. Samples were obtained at one station aIong the entire water column (60 m) with a, Van Doro sampler and filtered througha 55 μm mesh. Copepod densities were evaluated. Vertical pro files of temperature, dissolved oxygen, pH, specific conductivity (K2S), and chlorophyll a concentrations were measured. Lake Alchichica limnetic area is hyposaline (K25=13000μS cm-1 .8.5 g l.1), basic (pH 8.6-9.2) and oligo-mesolrophic (0-17:7 mg m-1 of chlorophyll a concentration). The lake is warm moqomictic and circulates during the cold season (winter-spring). L. novamexicanus was the only crustacean zooplankton species inhabiting the limnetic area of the lake. Copepod densities ranged between O and 267 org l-1. A significative difference in copepod densities was observed between circulation (66.91±75.62 copepods l-1, main ± 1 s.d.) and stratification-(1S.83±32.43 copepods l-1) period, and between the upper (0-30 ID, 44.54±64.64 copepods l-1) and lewerstrata (40-60 m, 19.77±43,88 copepods l-1) of the lake. Maximum copepod densities coincided with the presence of two pytoplankton blooms: a diatom bloom in January (chlorophyll a 4.1-8.5 mg m-3 ), and after wards, a cyanobacterial bloom (chlorophyll a 1.4-17.7 mg m-3), in May. Highest valuesof copepod densities were found between 10-15 m depth, within tbe photic zone (20-25, m) Df the lake. L. novamexicanus population of Lake Alclhichica limnetic zone might live under low interspecific competition conditions due to the absence ofother crustaceari zooplanktic species. Under these circumstances vertical and temporal fluctuations of this copepod population mainly depends on environmental conditions¡ basically on the periods of circulation-stratification) of the lake that influence food availability.